(How) Do You Regret Killing One to Save Five? Affective and Cognitive Regret Differ After Utilitarian and Deontological Decisions. (September 2020) - Goldstein-Greenwood, Jacob; Conway, Paul; Summerville, Amy; Johnson, Brielle N.
Sacrificial moral dilemmas, in which opting to kill one person will save multiple others, are definitionally suboptimal: Someone dies either way. Decision-makers, then, may experience regret about these decisions. Past research distinguishes affective regret, negative feelings about a decision, from cognitive regret, thoughts about how a decision might have gone differently. Classic dual-process models of moral judgment suggest that affective processing drives characteristically deontological decisions to reject outcome-maximizing harm, whereas cognitive deliberation drives characteristically utilitarian decisions to endorse outcome-maximizing harm. Consistent with this model, we found that people who made or imagined making sacrificial utilitarian judgments reliably expressed relatively more affective regret and sometimes expressed relatively less cognitive regret than those who made or imagined making deontological dilemma judgments. In other words, people who endorsed causing harm to save lives generally felt more distressed about their decision, yet less inclined to change it, than people who rejected outcome-maximizing harm.